Relationship between Tactics and Energy Expenditure According to Level of Experience in Badminton. Issue 2 (October 2014) - Dieu, Olivier; Vanhelst, Jérémy; Bui-Xuân, Gilles; Blondeau, Thomas; Fardy, Paul S.; Mikulovic, Jacques
Research on racket sports has traditionally focused on expert players and has treated energy expenditure and tactics as independent factors. These prior studies could not assess how energy expenditure and tactics changed as a function of experience and skill. Here, the specific relationship between playing tactics and energy expenditure in badminton were assessed. Participants were classified into five stages of badminton experience on the basis of conative criteria: structural (physical abilities), technical (technical skills), and functional (tactics). The physical activity of 99 players (47 beginners, 15 intermediates, 30 advanced, and 7 experts) was measured using a three-axis accelerometer during a badminton set (21 points, no extra scoring). The results showed that physical activity (counts/sec.) ranged between about 115 (Stage 1) and 155 (Stage 5), and differed significantly across the conative stages. For Stages 2 and 4, defined by an increase in use of tactics, physical activity increased substantially. For Stage 3, defined by a decrease in use of tactics, physical activity decreased significantly. Thus, tactically-oriented play appears to be closely related to physical activity.